Investigating the impact of ICT Professional Development of Six South African Primary School Teacher’s Innovation in Curriculum Delivery - Maeane, Matjema Caroline (University of the Witwatersrand, Johannesburg, 2024)
Despite ministerial efforts to advance education standards through the development of ICT policies aimed at encouraging and guiding ICT integration in teaching, teachers in various South African schools still lack the necessary digital skills and proficiencies to deliver the curriculum innovatively using ICTs. This lack of skill is often attributed to the ineffectiveness of previous ICT-Teacher Professional Development (TPD) training programmes, which failed to produce the desired outcomes of ICT innovation among teachers. In response to this challenge, this study investigated the effectiveness of a newly developed ICT-TPD programme, which was informed by a combination of key theories: Rogers’ Diffusion of Innovation Theory, Constructivism Learning Theory, Self Determination Theory (SDT), and Community of Practice (CoP) Theory. These theories guided the facilitation process of the Professional Development (PD) training programme. The study focused on assessing the ICT innovation levels of six teachers from a primary school in urban Johannesburg, South Africa, by surveying their innovation levels before and after the ICT-TPD intervention. To support the content delivery and the development of teachers’ ICT competencies, the TPD programme further employed the Gradual Release of Responsibility Model (GRRM) and the Concerns-Based Adoption Model (CBAM). For a more comprehensive understanding of the dataset and its implications, mixed-methods were employed to triangulate the quantitative and qualitative data collection and analysis procedures derived from this study. Questionnaires, interviews, and a criterion assessment rubric were used to gather data from participants. This was followed by a mixed-methods sequential explanatory design used to collect and analyse data that was both qualitative and quantitative. A non-probability purposeful sampling technique was further employed to identify participants who could offer rich, pertinent, and varied information on their experiences and opinions regarding the ICT training curriculum. Additionally, a theme analysis was used to identify, assess, and report on patterns in the qualitative data (Braun & Clarke, 2006). Finally, the quantitative data was analysed using exploratory statistical approaches to find underlying patterns and relationships within the dataset. The results from the study concluded that the ICT-TPD had a desired impact, to promote innovative pedagogical practices through the integration of ICTs, as well as resulted in the improvement of teachers’ overall innovation levels. The sampled primary school teachers displayed resilience and dedication in engaging with the ICT-TPD programme for the benefit of their professional development, despite facing challenges such as resource and time constraints. According to the study, including its results and related theory, however, it is recommended that while there is evidence of achieving positive results from the ICT-TPD intervention, the long-term effective ICT integration for innovative pedagogical practice necessitates a more continuous professional growth approach through similar interventions, collaborative learning, and alignment with educational goals. Lastly, the study further emphasises the importance of recognising primary school teachers’ intrinsic and extrinsic motivations and addressing the related challenges through targeted support to enhance the effectiveness and sustainability of the ICT-TPD programmes, which ultimately benefits the primary school students’ learning experiences and eventual innovative outcomes.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Innovation/ Pedagogical innovation; ICT; ICT integration; Professional development (PD); Training approaches; Curriculum delivery; and ICT-TPD; SDG-4: Quality education